The role of mobile phones as a possible pathway for pathogen movement, a cross-sectional microbial analysis. Issue 43 (September 2021) - Tajouri, Lotti; Campos, Mariana; Olsen, Matthew; Lohning, Anna; Jones, Peter; Moloney, Susan; Grimwood, Keith; Ugail, Hassan; Mahboub, Bassam; Alawar, Hamad; McKirdy, Simon; Alghafri, Rashed
Abstract: Introduction: Mobile phones are used the world over, including in healthcare settings. This study aimed to investigate the viable microbial colonisation of mobile phones used by healthcare personnel. Methods: Swabs collected on the same day from 30 mobile phones belonging to healthcare workers from three separate paediatric wards of an Australian hospital were cultured on five types of agar plate, then colonies from each phone were pooled, extracted and sequenced by shotgun metagenomics. Questionnaires completed by staff whose phones were sampled assisted in the analysis and interpretation of results. Results and discussion: All phones sampled cultured viable bacteria. Overall, 399 bacterial operational taxonomic units were identified from 30 phones, with 1432 cumulative hits. Among these were 58 recognised human pathogenic and commensal bacteria (37 Gram-negative, 21 Gram-positive). The total number of virulence factor genes detected was 347, with 1258 cumulative hits. Antibiotic resistance genes (ARGs) were detected on all sampled phones and overall, 133 ARGs were detected with 520 cumulative hits. The most important classes of ARGs detected encoded resistance to beta-lactam, aminoglycoside and macrolide antibiotics and efflux pump mediated resistance mechanisms. Conclusion: Mobile phones carry viable bacterial pathogens and may act as fomites by contaminating the hands of their users and indirectly providing a transmission pathway for hospital-acquired infections and dissemination of antibiotic resistance. Further research is needed, but meanwhile adding touching mobile phones to the five moments of hand hygiene is a simple infection control strategy worth considering in hospital and community settings. Additionally, the implementation of practical and effective guidelines to decontaminate mobile phone devices would likely be beneficial to the hospital population and community at large.